Implementation of the Social Rehabilitation Assistance Program in an Effort to Empower Persons with Disabilities Through Entrepreneurship Development Initiation Activities by the Sentra Bahagia in Asahan District - Affandi, Ade Zul; Bengkel, Bengkel; Siregar, Hairani (East Asian Journal of Multidisciplinary Research, 2024)
The social rehabilitation assistance program for people with disabilities aims to enhance the ability of individuals, families, and communities to meet basic needs, perform social roles, and address life challenges. Sentra Bahagia Medan, a unit under the Ministry of Social Affairs, implemented such a program in Asahan Regency through pastry-making training in April 2023. This qualitative descriptive study, involving 15 beneficiaries, analyzes the program's impact and factors influencing empowerment through entrepreneurial development activities. Findings reveal that while participation was high, beneficiaries' independence remains limited, and the sustainability of businesses initiated through the program is suboptimal. Recommendations include better assessment, stronger commitment, increased support, and consideration of beneficiaries' backgrounds.